Improving Students’ Vocabulary Mastery By Using Riddle Games - Megi, (Jurnal Serambi Ilmu, 2024)
The purpose of this study is (1) to find out whether the use of riddles results in an effective game in improving students' vocabulary. (2) What is the significance of students' responses when learning vocabulary using riddle games? This study used a quasi-experimental design. The number of students in the school was 38 students. This research technique used purposive sampling. The researcher's sample amounted to 20 students from class IX. The class was then divided into two levels experiment and control. Data analysis was conducted using student vocabulary tests to obtain students' vocabulary performance, which was then analyzed using inferential statistics using SPSS version 22. The post-test score at the end of the experiment was significantly higher than the pre-test score which was 70.50>59.50. The difference between the two scores was statistically significant. Based on the test results at a significant level of 0.05, the probability of the results is greater than the significant threshold (0.02<0.05). H1 is accepted and H0 is rejected. It can be stated that the use of riddles is an effective game to improve students' vocabulary, and students also give positive feedback when learning vocabulary using riddles.